Local and global genetic diversity of protozoan parasites: Spatial distribution of Cryptosporidium and Giardia genotypes. - Juan C Garcia-R; Nigel French; Anthony Pita; Niluka Velathanthiri; Rima Shrestha; David Hayman (Public Library of Science (PLoS), 2017)
Cryptosporidiosis and giardiasis are recognized as significant enteric diseases due to their long-term health effects in humans and their economic impact in agriculture and medical care. Molecular analysis is essential to identify species and genotypes causing these infectious diseases and provides a potential tool for monitoring. This study uses information on species and genetic variants to gain insights into the geographical distribution and spatial patterns of Cryptosporidium and Giardia parasites. Here, we describe the population heterogeneity of genotypic groups within Cryptosporidium and Giardia present in New Zealand using gp60 and gdh markers to compare the observed variation with other countries around the globe. Four species of Cryptosporidium (C. hominis, C. parvum, C. cuniculus and C. erinacei) and one species of Giardia (G. intestinalis) were identified. These species have been reported worldwide and there are not unique Cryptosporidium gp60 subtype families and Giardia gdh assemblages in New Zealand, most likely due to high gene flow of historical and current human activity (travel and trade) and persistence of large host population sizes. The global analysis revealed that genetic variants of these pathogens are widely distributed. However, genetic variation is underestimated by data biases (e.g. neglected submission of sequences to genetic databases) and low sampling. New genotypes are likely to be discovered as sampling efforts increase according to accumulation prediction analyses, especially for C. parvum. Our study highlights the need for greater sampling and archiving of genotypes globally to allow comparative analyses that help understand the population dynamics of these protozoan parasites. Overall our study represents a comprehensive overview for exploring local and global protozoan genotype diversity and advances our understanding of the importance for surveillance and potential risk associated with these infectious diseases.